Brief Dutch design manual for bicycle and pedestrian bridges. English summary of the CROW design guide. - Berg, Christa van den (My University, 2015)
Die Publikation ist die englischsprachige Kurzfassung von: "Ontwerpwijzer bruggen langzaam verkeer". CROW, 2014. (ROW publication; 342)
Keywords: Fahrradverkehr; Fußgängerverkehr; Verkehrsinfrastruktur; Brücke; Brückenart; Design; Verkehrslenkung; Brückengestaltung; Fahrradinfrastruktur